2009
DOI: 10.1007/s11738-009-0304-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of two antidiabetic species known as guarumbo: Cecropia obtusifolia and Cecropia peltata

Abstract: Two Cecropia species (Cecropia obtusifolia and C. peltata), known as guarumbo, are employed in Mexican traditional medicine to treat diabetes mellitus; the leaves of both species contain phenolic bioactive compounds such as chlorogenic acid (CA) and isoorientine (ISO), which have been attributed with hypoglycemic, hypolipidemic, and antioxidant properties. An in vitro propagation protocol was developed from existing apical bud meristem from C. obtusifolia seedlings; the shoot generation was induced on Murashig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…This specimen was identified (code number 14123) by Abigail Aguilar, Director of the Mexican Institute of Social Security's (IMSSM) medical plants herbarium of Mexico (Nicasio-Torres et al 2009). Seeds were surface sterilized by successive immersion in 70% ethanol for 5 min, which was followed by immersion in a commercial bleach solution (Cloralex Ò :water, 1:5 v/v) for 10 min.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This specimen was identified (code number 14123) by Abigail Aguilar, Director of the Mexican Institute of Social Security's (IMSSM) medical plants herbarium of Mexico (Nicasio-Torres et al 2009). Seeds were surface sterilized by successive immersion in 70% ethanol for 5 min, which was followed by immersion in a commercial bleach solution (Cloralex Ò :water, 1:5 v/v) for 10 min.…”
Section: Plant Materialsmentioning
confidence: 99%
“…HPLC analyses for CGA (Sigma Chemical Co., St Louis, MO, USA) and ISO (Indofine Chemical Co., Inc., USA) were conducted on a Waters (Separation Module 2695) HPLC with a system controller (Millennium System Manager Software) and under conditions previously established by Nicasio-Torres et al (2009). Samples (60-ll) were eluted onto a Spherisorb ODS-2 column (250 mm 9 4.6 mm, 5 lm) at a 1 ml min -1 flow rate with a binary gradient of mobile phases as follows: (A) H 2 O-(H 3 PO 4 0.5%), and (B) CH 3 CN-CH 3 OH (1:1) within 32 min.…”
Section: Hplc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many plants are grown under in vitro conditions to conserve the germplasm, examples are micropropagation of Cecropia spp. (Nicasio-Torres et al 2009), Ceropegia intermedia (Karuppusamy et al 2009), Bacopa monnieri (Singh et al 2009), Asparagus racemosus (Bopana and Saxena 2008) and Searsia dentata (Prakash and Van Staden 2008). In some cases, tissue and cell culture is also used for the production of interesting secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these species have been used for diabetes and other ailments in Latin America and elsewhere, though for C. peltata, its congeneric C. obtusifolia is more widely known and used Ferreira et al 2012;Nicasio-Torres et al 2009;Quanico et al 2008). One study (Nicasio-Torres et al 2009) of the antidiabetic activity of Cecropia species suggested that the phenolics chlorogenic acid and isoorientin that were isolated from their extracts were responsible for their activity.…”
Section: Discussionmentioning
confidence: 99%